Prevalence of Trachoma in Niger State, North Central Nigeria: Results of 25 Population-Based Prevalence Surveys Carried Out with the Global Trachoma Mapping Project. (7th December 2016) - Adamu, Mohammed Dantani; Mpyet, Caleb; Muhammad, Nasiru; Umar, Murtala Muhammad; Muazu, Habila; Olamiju, Francisca; Isiyaku, Sunday; Onyebuchi, Uwazoeke; Bosso, Usman Abubakar; William, Adamani; Nwobi, Benjamin C.; Willis, Rebecca; et al.
ABSTRACT: Purpose : To determine the prevalence of trachoma in each of the 25 local government areas (LGAs) of Niger State, Nigeria. Methods : A population-based cross-sectional survey was conducted in each Niger State LGA between March and April 2014, as part of the Global Trachoma Mapping Project (GTMP). GTMP protocols were used in planning and conduct of the surveys. Using probability proportional to size, 25 clusters were selected; in each of these clusters, 25 households were enrolled for the survey. All residents aged 1 year and older were examined by GTMP-certified graders for trachomatous inflammation – follicular (TF) and trichiasis using the World Health Organization simplified grading scheme. Additionally, we collected data on household water and sanitation facilities. Results : Only one LGA (Kontagora) had TF prevalence in 1–9-year-olds above 10%; one other LGA (Rafi) had TF prevalence between 5.0 and 9.9%. Six LGAs need trichiasis surgical services provided to achieve a prevalence of <1 case of trichiasis per 1000 total population. The proportion of households with access to improved water sources ranged from 23 to 100%, while household-level access to improved latrines ranged from 8 to 100% across the LGAs. Conclusion : The prevalence of trachoma is relatively low in most of Niger State. There is a need for community-based trichiasis surgical services in a small number of LGAs. The trachoma elimination program could engage water and sanitation agencies to augment access to improved water and sanitation facilities, for human rights reasons. Kontagora and Rafi need community-based interventions to reduce the prevalence of active trachoma.